Exploring HR Experiences at Bunda Sarini Clinic: Digitalization, MIS, Service Quality, and Operational Efficiency - Giovanni Owen Nanda Wijaya; Eddy Yunus; Meithiana Indrasari (Journal of International Multidisciplinary Research, 2025)
The integration of digitalization and Management Information Systems (MIS) has profoundly enhanced human resource efficiency, service quality, and operational effectiveness at Klinik Pratama Bunda Sarini. This study explores the role of MIS in optimizing workforce management and improving patient-centered care, highlighting both its advantages and the challenges encountered during implementation. Researchers employed a qualitative case study approach, utilizing semi-structured interviews and document analysis to examine HR professionals' experiences with digital transformation. The findings indicate that MIS has streamlined administrative workflows, reduced clerical inefficiencies, and improved real-time data accessibility, facilitating faster decision-making and higher patient satisfaction. However, workforce resistance, digital literacy limitations, and data security concerns created obstacles in the transition process. Structured HR-led training programs and phased implementation strategies effectively addressed these challenges. The study underscores the importance of sustained investment in workforce development, cybersecurity measures, and digital infrastructure to support long-term healthcare digitalization. Future research should evaluate the long-term impact of digital adoption in small-scale healthcare institutions.